2023
DOI: 10.1186/s40246-023-00491-7
|View full text |Cite
|
Sign up to set email alerts
|

A heterozygous mutation in UBE2H in a patient with developmental delay leads to an aberrant brain development in zebrafish

Abstract: Background Ubiquitin-related rare diseases are generally characterized by developmental delays and mental retardation, but the exact incidence or prevalence is not yet fully understood. The clinical application of next-generation sequencing for pediatric seizures and developmental delay of unknown causes has become common in studies aimed at identification of a causal gene in patients with ubiquitin-related rare diseases that cannot be diagnosed using conventional fluorescence in situ hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Additionally, Ube2S is controlled by the PTEN/Akt pathway and participates in DNA repair, particularly NHEJ-mediated DNA repair, which makes chemotherapeutic drugs more sensitive to GBM ( Maksoud, 2021 ). In a recent study, Shin et al found a mutation ( de novo missense variant) that resembles a variant found in a patient with neurodevelopmental abnormalities, induces irregular Ube2h function in zebrafish embryos, and results in abnormal brain development ( Shin et al, 2023 ). In addition, according to Lim and Joo (2020) , circulating Ube2H mRNA is potentially used to diagnose and treat Alzheimer’s disease ( Lim and Joo, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Ube2S is controlled by the PTEN/Akt pathway and participates in DNA repair, particularly NHEJ-mediated DNA repair, which makes chemotherapeutic drugs more sensitive to GBM ( Maksoud, 2021 ). In a recent study, Shin et al found a mutation ( de novo missense variant) that resembles a variant found in a patient with neurodevelopmental abnormalities, induces irregular Ube2h function in zebrafish embryos, and results in abnormal brain development ( Shin et al, 2023 ). In addition, according to Lim and Joo (2020) , circulating Ube2H mRNA is potentially used to diagnose and treat Alzheimer’s disease ( Lim and Joo, 2020 ).…”
Section: Resultsmentioning
confidence: 99%